2021
DOI: 10.47836/pjssh.29.4.10
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Food Safety Knowledge on Organic Food Purchase Intention in a New Normal

Abstract: The emergence of a ‘new normal’ life caused by pandemic Coronavirus Disease (COVID-19) leads to consumer perception and business practices changes. However, there is limited data on the current market demand and condition on consumer purchase intention of organic food associated with food safety knowledge. Thus, this study aimed to examine consumer perception toward organic food in a new normal life. A total of 330 valid responses were received for analysis using Structural Equation Modelling (SEM) and PROCESS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…In addition, future study should assess real knowledge, such as through a knowledge test. According to Abdul Latip et al (2021) , studies on organic food purchases from the lens of consumers must be conducted on a consistent interval in order to understand consumer intent and demand.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In addition, future study should assess real knowledge, such as through a knowledge test. According to Abdul Latip et al (2021) , studies on organic food purchases from the lens of consumers must be conducted on a consistent interval in order to understand consumer intent and demand.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Together, these three determinants can influence a person's intention to perform a particular behaviour. For instance, a person who strongly believes that performing a specific behaviour will lead to positive outcomes (behaviour belief), who feels social pressure to perform that behaviour (normative belief) and who believes that they have the necessary resources to carry out the behaviour (control belief) is more likely to have a stronger intention to perform that behaviour (Latip et al , 2021; May and Latip, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Personal attitude refers to a set of beliefs, emotions and behaviours towards a particular object, thing, person or others (Ajzen, 1991). It is a crucial factor that can influence individuals' behaviour, as their attitude towards something can shape their thoughts, feelings and actions related to that thing (Cherry, 2018; Latip et al , 2021). Previous studies have shown that a person's attitude is influenced by their perception of the consequences of executing the action and how it potentially affects the positive or negative feelings an individual associates with the behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations